THE FORM OF SENSUALITY IN HISPANIC MUSIC IN AMERICAN MUSIC INDUSTRY: DISCOURSE ANALYSIS ON AMERICAN POPULAR MUSIC - Maria Elfrieda C.S.T; Ida Rochani Adi (Rubikon : Journal of Transnational American Studies, 2020)
In 2017 and 2018, Hispanic music reaches high popularity as world music. The reaction came from the American music industry, seen through the production of Hispanic music in American music industry, which brings Hispanic music as a part of American popular music. In this case, American popular musicians started to produce music that contains Hispanic music characteristics. Among all of the characteristics, the form of sensuality becomes a significant aspect in producing Hispanic music, even in American music industry. In relation to this fact, this research is conducted in order to see how the form of sensuality supports the popularity of Hispanic music. The theory of Discourse Analysis by Michel Foucault is applied to analyze sensuality as adiscourse behind the popularity of Hispanic music. As a research conducted within the frame of American Studies, this research also usesthe postmodern approach to see the new formula related to the form of sensuality in Hispanic music, especially when produced in the American music industry.